Biochars derived from bamboo and rice straw for sorption of basic red dyes - Sackey, Ebenezer Ampofo; Song, Yali; Yu, Ya; Zhuang, Haifeng (PloS one, 2021)
The primary purpose of this study is to eliminate Basic Red 46 dye from aqueous solutions utilizing batch experiments by adsorption on biochars prepared from bamboo and rice straw biomass. Biochars prepared from bamboo (B), and rice straw (R) was pyrolyzed at 500°C (B500 and R500). Scanning Electron Microscopy (SEM), Fourier Transform Infrared (FTIR) Spectroscopy, X-ray Diffraction (XRD), and surface area and porosity analyzers were used to characterize the B500 and R500 samples. The characterization results indicated that the biochars possessed an amorphous porous structure with many functional groups consisting primarily of silicates. The adsorption rate of BR46 was evaluated using two kinetic models (pseudo-first-order and pseudo-second-order), and the results indicated that the pseudo-second-order model fitted to the experimental data well (R 2 >0.99). Nearly 24 h was sufficient to achieve equilibrium with the dye adsorption for the two biochars. R500 had a greater adsorption efficiency than B500. As pH levels increased, the dye’s adsorption capability increased as well. The Langmuir and Freundlich isotherm models were used to investigate the equilibrium behavior of BR46 adsorption, and the equilibrium data fitted well with the Langmuir model (R 2 >0.99) compared to the Freundlich model (R 2 >0.89). The maximum adsorption capacities of BR46 are 9.06 mg/g for B500 and 22.12 mg/g for R500, respectively. Additionally, adsorption capacity increased as temperature increased, indicating that adsorption is favored at higher temperatures. The electrostatic interaction is shown to be the dominant mechanism of BR46 adsorption, and BR46 acts as an electron-acceptor, contributing to n-π EDA (Electron Donor-Acceptor) interaction. Thermodynamic parameters for the dye-adsorbent system revealed that the adsorption process is spontaneous and feasible. The values of the adsorption coefficient (K d ) were on the order of 10 2 −10 3 . K d of R500 was greater than that of B500, indicating that R500 had a greater adsorption capacity. The results showed that R500 could be used as a low-cost alternative adsorbent for removing BR46 from effluents.